2007
DOI: 10.1086/518823
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Accretion Disk X‐Ray Continuum of Black Hole Candidates

Abstract: We critically examine issues associated with determining the fundamental properties of the black hole and the surrounding accretion disk in an X-ray binary based on modeling the disk X-ray continuum of the source. We base our work mainly on two XMM-Newton observations of GX 339−4, because they provided high-quality data at low energies (below 1 keV), which are critical for reliably modeling the spectrum of the accretion disk. A key issue examined is the determination of the so-called "color correction factor",… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…COMPTT in Xspec). For example, Pszota & Cui (2007) infer f ∼ 1.3 − 1.5, broadly consistent with models discussed below.…”
Section: Introductionsupporting
confidence: 76%
“…COMPTT in Xspec). For example, Pszota & Cui (2007) infer f ∼ 1.3 − 1.5, broadly consistent with models discussed below.…”
Section: Introductionsupporting
confidence: 76%
“…As was mentioned above, their method requires prior knowledge of several other factors including the inner‐disc inclination and distance to the source. Pszota & Cui (2007) have recently shown that neither disc continuum models KERRBB (Li et al 2005) nor BHSPEC (Davis & Hubeny 2006) were able to successfully model the ultrasoft spectra of GX 339−4, nonetheless their best‐fitting parameters in conjunction with the best estimates for the physical parameters of the source suggested a moderate spin of 0.5–0.6 in comparison with our estimate of ≈0.935 (Miller et al 2008a; Reis et al 2008) based on the various reflection features in the spectra of GX 339−4. Our suggestion that J1655−40 contains a rapidly rotating black hole is in agreement with results based on quasi‐periodic oscillations where a value of >0.91 is usually derived (Zhang, Cui & Chen 1997; Cui, Zhang & Chen 1998; Wagoner, Silbergleit & Ortega‐Rodríguez 2001; Rezzolla et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The high-quality data below 1 keV enable the reliable modeling of the accretion disk, while the high energy data help to constrain the parameters of the hard component. In Some of the previously mentioned issues were addressed in our 2007 work [40], where XMM-Newton and RXTE data from the 2002-2003 outburst of GX 339-4 were jointly fitted, covering an energy range of 0.5-150 keV (2002 dataset) and 0.5-60 keV (2003 dataset). The source was in its very high state in 2002 and in the high/soft state in 2003.…”
Section: Review Of the Recent Research On Gx 339-4mentioning
confidence: 99%
“…This is a self-consistent model of reflection from the hot inner portion of an accretion disk, which also includes the blackbody radiation of the disk, in case of a constant density atmosphere in hydrostatic equilibrium. The statistics (𝜒 /dof = 1.48/1718) are still not perfect, but there is definitely a big improvement compared to the quality of our fit in [40], when the kerrbb or bhspec model was used for a similar dataset. The reflection model showed only a weak contribution due to the Fe Kα emission, which The inclination was fixed at the 51 • value obtained from the laor model, which was utilized for the best fit of the 2003 dataset, the mass of the BH was set to 10 M ò, and the distance to the source to 8 kpc.…”
mentioning
confidence: 91%
See 1 more Smart Citation